First-in-human study to investigate the safety and pharmacokinetics of salvianolic acid A and pharmacokinetic simulation using a physiologically based pharmacokinetic model - Chen, Jinliang; Ruan, Zourong; Lou, Honggang; Yang, Dandan; Shao, Rong; Xu, Yichao; Hu, Xinhua; Jiang, Bo (Frontiers in Pharmacology, 2022)
Salvianolic acid A (SAA) is a water-soluble phenolic acid component from Salvia miltiorrhiza Bunge currently under development for myocardial protection treatment in coronary heart disease (CHD). We investigated the safety, tolerability, and pharmacokinetics of single and multiple ascending doses of SAA. Additionally, a physiologically based pharmacokinetic (PBPK) model was developed to simulate the pharmacokinetics of SAA. This was a first-in-human (FIH), randomized, double-blind, placebo-controlled, single, and multiple dose study in 116 healthy Chinese subjects with the range of 10–300 mg and 60–200 mg SAA, respectively. SAA was well tolerated at all dose levels following both single and multiple doses, with a low overall incidence of treatment emergent adverse events (TEAEs) which appeared to be no dose related. The main pharmacokinetic parameters of SAA, assessed by the power model, were lack of proportionality with dose range after single dosing. The 90% CIs of the slope 𝛽 of Cmax (1.214 [1.150–1.278]) and AUC0-t (1.222 [1.156–1.288]) were not within the predefined acceptance range, and the direction of the deviation was high than expected. PBPK modeling suggested the transfer ability saturation of hepatic organic anion-transporting polypeptide 1B1 (OATP1B1) and P-glycoprotein (P-gp) might result in relative low distribution rate at higher doses. Clinical plasma concentrations observed were in good agreement with PBPK prediction. SAA showed well-characterized pharmacokinetics and generally well tolerated in the dose range investigated. The PBPK model provides valuable pharmacokinetic knowledge for further clinical development.